2012
DOI: 10.1183/09059180.00003912
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of pulmonary hypertension: standard operating procedure

Abstract: Patients with suspected pulmonary hypertension (PH) should be evaluated using a multimodality approach to ensure that they receive a correct diagnosis. The series of investigations required includes clinical evaluation, noninvasive imaging techniques and right heart catheterisation (considered to be the ''gold standard'' for the diagnosis of PH). Current guidelines recommend that a detailed echocardiographic assessment is performed in all patients with suspected PH.In this review we summarise a protocol adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 54 publications
2
160
0
8
Order By: Relevance
“…4, 5 The measurement of MPAPPR becomes more difficult with the anatomical modifications of right ventricular (RV) structure in patients with severe PH. Chemla et al reported that MPAP can be reliably calculated from SPAP estimated from the peak flow velocity of TR (SPAPTR) using the formula: MPAP=0.61×SPAPTR+2 mmHg.…”
mentioning
confidence: 99%
“…4, 5 The measurement of MPAPPR becomes more difficult with the anatomical modifications of right ventricular (RV) structure in patients with severe PH. Chemla et al reported that MPAP can be reliably calculated from SPAP estimated from the peak flow velocity of TR (SPAPTR) using the formula: MPAP=0.61×SPAPTR+2 mmHg.…”
mentioning
confidence: 99%
“…The absence or failure to get alignment of TR jet mandates the use of PR Doppler profile, if present, to estimate the MPAP and DPAP. The MPAP can be obtained from the PR velocity at the beginning of regurgitation as MPAP = 4 × [Beginning velocity of pulmonary regurgitation jet (Vpr)] 2 + Pra, and the DPAP from the end diastolic velocity of PR as DPAP = 4 × (End Vpr) 2 + right atrial pressure (Pra), where Pra is end diastolic pressure in right atrium, 23 which has the similar limitations that PR is not always present in all the patients. The dependency on the presence of TR and PR in the above-mentioned methods made the use of pulmonary flow contour analysis in estimating MPAP, which is available in all patients even in populations without any cardiopulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since the RVET has negative correlation with the HR, thereby, indirectly affecting the PAT, Howard et al 23 suggested a correction in PAT value according to the patient's HR, when HR >100 or <70, which is done by multiplying the PAT by 75 and dividing by the patient's HR.…”
Section: Jopementioning
confidence: 99%
“…7 On the basis of these three parameters (dilation, hypertrophy and contractility), an experienced echo cardiographer will be able to make a good qualitative assessment of RV function and will be able to grade it as mild,moderate or severe impairment. 8 A good evaluation of pulmonary haemodynamics can be performed with Doppler echocardiography using in association, several measurements,for example: maximal velocity of TR,pulmonary blood flow velocity and new indices of right ventricular dysfunction. 9 The triad of decreased RV systolic function, increasing RV sizeand septal bowing form the fundamental basis for the echocardiographic recognition of PAH, with or without demonstration of an increase in Doppler estimated PA systolic pressure.…”
Section: Discussionmentioning
confidence: 99%